EFFECT OF WORK DISCIPLINE, WORK STRESS AND LEADERSHIP ON EMPLOYEE PERFORMANCE PT PD PAJA PINANG MEDAN - Demak Claudia Yosephine Simanjuntak; Seren Seren; Ladina Afdilah (LLDIKTI Wilayah X, 2020)
The purpose of this study was to examine and anaIyze the effect of work discipline, work stress and leadership on empIoyee performance at PT PD Paja Pinang Medan. Employee indiscipline in following the provisions of working time and attendance has an impact on the high level of absenteeism and tardiness of employees working in the company. Work stress experienced by employees is caused by workload that is too much, pressure from superiors to always finish work on time and employee supervision that is too tight resulting in high levels of employee turnover in the company. Employee performance has decreased and has an impact on the non-achievement of sales targets for Crude Palm Oil and Palm Kernel. The population was 146 employees and the sampIe in this study was 107 employees. The research method uses muItiple Iinear regression anaIysis techniques. The calculation result of hypothesis testing partially obtained tcount> ttable or 4.504> 1.983 means that partially Work Discipline, Job Stress and Leadership have positive and significant effect on the Performance of EmpIoyees of PT PD Paja Pinang Medan. the results of the test obtained the caIculated F vaIue (21,658)> F tabIe (2.69) and a significance probabiIity of 0, 000 < 0. 05, meaning that simultaneous Work Discipline, Job Stress and Leadership have positive and significant effect on EmpIoyee Performance of PT PD Paja Pinang Medan